2020
DOI: 10.1089/aid.2018.0182
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Impairment in Well-Suppressed Children with Perinatal HIV-Infection on Antiretroviral Therapy

Abstract: Mitochondrial impairment is reported in HIV-infected children receiving antiretroviral therapy (ART), as well as those naive to ART. Whether mitochondrial function recovers with early initiation of ART and sustained viral suppression on long-term ART is unclear. In this study, we evaluate mitochondrial markers in wellsuppressed perinatally HIV-infected children initiated on ART early in life. We selected a cross-sectional sample of 120 HIV-infected children with viral load <400 copies/mL and 60 age-matched uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Mitochondrial function and substrate utilization are perturbed in young children with PHIV [96,97]. Despite early ART treatment and viral suppression, cross-sectional analyses suggest that young PHIV children (mean age ¼ 6 years) have mitochondrial impairment as measured by complex IV, citrate synthase and mitochondrial DNA content [97]. It is unclear, however, whether decades of ART will allow for recovery or further declines in mitochondrial function.…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…Mitochondrial function and substrate utilization are perturbed in young children with PHIV [96,97]. Despite early ART treatment and viral suppression, cross-sectional analyses suggest that young PHIV children (mean age ¼ 6 years) have mitochondrial impairment as measured by complex IV, citrate synthase and mitochondrial DNA content [97]. It is unclear, however, whether decades of ART will allow for recovery or further declines in mitochondrial function.…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…Long-acting ARV formulations [e.g., non-nucleoside reverse-transcriptase inhibitors, INSTIs, and TFV] have been tested in clinical trials, and the metabolic toxicities of these formulations are a concern [68]. Cumulative effects of cART may be particularly impactful in utero or in children and young adults with HIV, who currently require lifelong treatment and whose brain development is ongoing when therapy is initiated [69][70][71][72]. Our results also raise the possibility that chronic cellular iron accumulation due to HIV, and augmented by cART, contribute to cellular senescence and accentuated aging phenotypes in PWH [73,74], including increased brain aging and HAND.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, although not showing an association, identified CHEU with possible mitochondrial dysfunction based on neurologic manifestations including febrile or afebrile seizures and delay in cognitive development [ 28 ]. To our knowledge, only one study reported lower height-for-age Z-scores among HIV-infected children with lower mtDNA content and decreased complex IV enzymatic activity from the mitochondrial respiratory chain [ 29 ]. Children herein who accumulated ARV exposure during pregnancy and during the first year of life, had few health problems, growth impairment, or hematological abnormalities at six years of age.…”
Section: Discussionmentioning
confidence: 99%